Sosialisasi Tentang Pentingnya Kesadaran Lingkungan dan Kegiatan Pemberdayaan Ibu Rumah Tangga di Lingkungan RPTRA Abdi Praja - Anggraeni, Motika Dian; Sari, Anggun Puspita; Wati, Rika Sintia; Adhiyaksa, Cindy; Lonia, Eka; Amal, Ikhlasul; Rifaldi, Muhammad; Albrian, Muhammad; Hakiem, Fauzan; Cahyani, Zahra Attika (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
This socialization activity was carried out at the Abdi Praja RPTRA (Child-Friendly Open Public Space) with the aim of increasing environmental awareness and empowering housewives to improve the family economy. This program combines two important aspects Environmental Awareness, which includes training on waste management, energy conservation, and sustainable use of natural resources, and Economic Empowerment, which involves training in business skills, family financial management, and income-increasing strategies. By involving housewives as the main participants, this activity aims to optimize their role in managing the household and improving family welfare through a practical and community-based approach. The results of this socialization activity are expected to improve the understanding and skills of participants in both areas, so that they can implement beneficial changes at the family and community levels. Through the empowerment of housewives and strengthening environmental awareness, it is hoped that the Abdi Praja RPTRA will become a successful example in implementing the principles of sustainability and improving the family economy in local communities.